The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1177/2167702616646314
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ Stigma Attitudes Toward Internalizing and Externalizing Disorders

Abstract: Objective This study examined predictors of stigma attitudes toward common youth emotional behavioral problems to test the hypothesis that interdependent cultural values would be associated with differential stigma towards externalizing versus internalizing disorders. Furthermore, we examined whether problem-specific stigma attitudes would predict adolescent’s own self-reported manifestations of distress. Method 1224 Vietnamese American and European American adolescents completed measures of social distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 72 publications
1
12
0
Order By: Relevance
“…Differences in stigma by cultural aspects have also been found in other studies (Koschorke, Evans-Lacko, Sartorius, & Thornicroft, 2017). Although the study had national rather than regional representativeness, the differences found when comparing the perceptions between regions, which coincide with the differences found by other authors regarding countries, regions, and localities, are striking (Lau et al, 2016;Semrau, Evans-Lacko, Koschorke, Ashenafi, & Thornicroft, 2015). These differences could be explained by the sample characteristics, since in region IV, the study population was significantly younger and with more years of schooling in comparison with the other regions included in the study.…”
Section: Discussionsupporting
confidence: 77%
“…Differences in stigma by cultural aspects have also been found in other studies (Koschorke, Evans-Lacko, Sartorius, & Thornicroft, 2017). Although the study had national rather than regional representativeness, the differences found when comparing the perceptions between regions, which coincide with the differences found by other authors regarding countries, regions, and localities, are striking (Lau et al, 2016;Semrau, Evans-Lacko, Koschorke, Ashenafi, & Thornicroft, 2015). These differences could be explained by the sample characteristics, since in region IV, the study population was significantly younger and with more years of schooling in comparison with the other regions included in the study.…”
Section: Discussionsupporting
confidence: 77%
“…Although the fight against the stigmatization of mental disorder has come a long way in the past three decades (Moses, 2011), in many societies and cultures, stigma is still one of the main challenges faced by people with mental disorders and their families in many societies and cultures. Due to public stigma, people with mental disorders may be unable to go to work and school, be rejected by society, and experience social isolation (Catthoor et al, 2015; Lau et al, 2016). Even without experiencing public stigma, people with mental disorders can sometimes feel stigmatized due to self‐stigma.…”
Section: Introductionmentioning
confidence: 99%
“…Stigma is not only perceived from society, but individuals with mental disorders also internalize and direct common negative beliefs and attitudes held by society toward themselves (Catthoor et al, 2015; Gaziel et al, 2015; Kranke et al, 2011). This phenomenon referred to in the literature as internalized stigma, prevents individuals from seeking and continuing treatment, thus interfering with rehabilitation (Catthoor et al, 2015; Kranke et al, 2011; Lau et al, 2016; Mukolo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Language use items were adapted from the Adolescents Coping with Everyday Stress study (Lau et al, 2016). Three items captured language competency (e.g., “How well do you speak and understand this language?”), and two items captured frequency of language use (e.g., “How often to you speak this language with your friends?”).…”
Section: Methodsmentioning
confidence: 99%